Mentoring program and its impact on individuals' advancement in the Malaysian context - Azman Ismail; Muhammad Madi Bin Abdullah; Sebastian K. Francis (Journal of Industrial Engineering and Management (JIEM), 2009)
The literature on workplace training highlights that the mentoring program is an important employee development method practiced in successful organizations. The ability of mentors either informally or formally to implement the mentoring program activities may lead to higher individuals' psychosocial support and career development. The nature of this relationship is interesting, but the role of the mentoring program as a predicting variable of individuals' advancement (psychosocial support & career development) has been given less attention in mentoring program models especially in the Malaysian organizational context. Therefore, this study was conducted to examine the direct effect of a mentoring program on individuals' advancement using a 153 usable questionnaire gathered from employees who have worked in a public university in East Malaysia. The outcomes of regression analysis showed four important findings: Firstly, formal mentoring positively and significantly correlated with individuals' psychosocial support. Secondly, informal mentoring positively and significantly correlated with individuals' career development. Thirdly, formal mentoring positively and significantly correlated with individuals' career development. Fourthly, informal mentoring positively and significantly correlated with individuals' psychosocial support. The results have empirically confirmed that properly implemented mentoring programs can lead to increased individuals' advancement in the studied organization. In addition, implications and discussions are also elaborated.
Keywords: 650; formal mentoring; informal mentoring; career development; psychosocial support; Malaysia